2020
DOI: 10.1186/s12864-020-07206-5
|View full text |Cite
|
Sign up to set email alerts
|

Sperm miRNAs— potential mediators of bull age and early embryo development

Abstract: Background Sperm miRNAs were reported to regulate spermatogenesis and early embryonic development in some mammals including bovine. The dairy cattle breeding industry now tends to collect semen from younger bulls under high selection pressure at a time when semen quality may be suboptimal compared to adult bulls. Whether the patterns of spermatic miRNAs are affected by paternal age and/or impact early embryogenesis is not clear. Hence, we generated small non-coding RNA libraries of sperm collec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Our previous studies also showed that miR-202-5p expressed and regulated LIMK2 during the early spermatogonial stage in chickens [15]. Meanwhile, many miRNAs have been found in spermatozoa and have been shown to be expressed differently in high and poor fertility bulls [19][20][21][22]. Besides, a previous study showed that miRNA also regulates spermatogenesis in humans, mice, etc.…”
Section: Introductionmentioning
confidence: 86%
“…Our previous studies also showed that miR-202-5p expressed and regulated LIMK2 during the early spermatogonial stage in chickens [15]. Meanwhile, many miRNAs have been found in spermatozoa and have been shown to be expressed differently in high and poor fertility bulls [19][20][21][22]. Besides, a previous study showed that miRNA also regulates spermatogenesis in humans, mice, etc.…”
Section: Introductionmentioning
confidence: 86%
“…These sperm RNA modifications could alter RNA structure and thus the interactions between RNA, DNA and proteins, leading to potentially greater consequences and wide-ranging effects (Zhang et al, 2018 ). Wu et al ( 2020b ) identified distinct differences in sperm-borne miRNAs from bulls of different ages, several of which targeted genes expressed in early embryos. This newly appreciated role of the sperm as RNA-based carriers of hereditary information provides a promising angle with which to understand aging and the etiology of environmentally induced disease beyond the initial exposure.…”
Section: Transgenerational Epigenetic Inheritance In Livestock Speciementioning
confidence: 99%
“…We examined the expression level of potential genes which enriched in these significant terms. Considering that miRNA negatively regulates gene expression by degrading target mRNA (Wu et al, 2020), we found that the expression level of Pten was significantly increased at all developmental stages (Figure 4B); other genes, such as Jmy, were only upregulated on Day2, while Bbc3 and Cdk19 were downregulated firstly and upregulated on Day3.5 (Figures 4C-F). We also detected some downregulated target genes of miR-148b-3p on Day1 and Day2, including Esr1, Robo1, and Ino80, and on Day3.5 including Robo1, Ino80, and Arpp19 (Figures 4G-Y).…”
Section: Validation Of Key Mirnas and Target Genes In Different Stages Of Embryonic Developmentmentioning
confidence: 99%